Evaluating IT Governance Capability in Managing Operational Contracts under PSAK 72: A Case Study of PT. XYZ's Government Service Division - Suhanda, Kezia Victoria; Faza, Ahmad (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
This research explores the evaluation of IT governance capability in managing operational contracts under PSAK 72 within PT. XYZ's Government Service Division (DGS). The study adopts the COBIT 2019 framework and the Gallegos method, focusing on three selected domains: EDM03, APO14, and DSS06. Interviews and questionnaires were used to assess current capability levels and identify areas for improvement. Results indicate that EDM03 and APO14 currently stand at level 2, while DSS06 is at level 4, falling short of their respective targets. Operational challenges in the LGS segment, such as missing contract data, affect PSAK 72 compliance and employee incentives. The study proposes recommendations to enhance documentation practices and IT risk evaluation. The usage of COBIT 2019's design factors provides a clearer focus on problem areas, making implementation more straightforward compared to COBIT 5. Addressing these challenges will optimize IT usage and ensure adherence to PSAK 72 requirements.